2000
DOI: 10.1093/emboj/19.17.4688
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a new isoform of the human estrogen receptor-alpha (hER-alpha) that is encoded by distinct transcripts and that is able to repress hER-alpha activation function 1

Abstract: A new isoform of the human estrogen receptor-alpha (hER-a) has been identi®ed and characterized. This 46 kDa isoform (hERa46) lacks the N-terminal 173 amino acids present in the previously characterized 66 kDa isoform (hERa66). hERa46 is encoded by a new class of hER-a transcript that lacks the ®rst coding exon (exon 1A) of the ER-a gene. We demonstrated that these D1A hER-a transcripts originate from the E and F hER-a promoters and are produced by the splicing of exon 1E directly to exon 2. Functional analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
315
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 369 publications
(336 citation statements)
references
References 61 publications
16
315
0
3
Order By: Relevance
“…Another possibility is that the key of neuroprotective effects of estradiol is related to the ER67/ER47 ratio, which is supported by Flouriot et al (Flouriot et al 2000). Our previous results showed that this ratio depends on the region of the brain that is studied.…”
Section: Nuclear Location Of Erα (Arrows) Citoplasmmatic Location Ofsupporting
confidence: 61%
See 1 more Smart Citation
“…Another possibility is that the key of neuroprotective effects of estradiol is related to the ER67/ER47 ratio, which is supported by Flouriot et al (Flouriot et al 2000). Our previous results showed that this ratio depends on the region of the brain that is studied.…”
Section: Nuclear Location Of Erα (Arrows) Citoplasmmatic Location Ofsupporting
confidence: 61%
“…However, the value experiments a decrease in normal aged and in ovariectomized animals from 12 months of treatment (Alonso et al 2008). In this sense, in cell cultures it has been described as an ER67/ER47 ratio lower in proliferating cells than in quiescent or non-proliferating cultures, so when the culture is young and healthy the value of the ratio is low (Flouriot et al 2000). There is a strong possibility that a compensatory mechanism was activated by the low levels of estrogen; 17β-estradiol treatment induces a progressive increase of this parameter from the beginning to the end of the experimental period, though the value never reaches up to those of the OVX group.…”
Section: Nuclear Location Of Erα (Arrows) Citoplasmmatic Location Ofmentioning
confidence: 99%
“…ESR1-66 may be encoded by mRNAs that are transcribed from all six ESR1 gene promoters, whereas ESR1-46 is encoded only by mRNAs transcribed from promoters located upstream of exon E1 or F (Figure 1) (Flouriot et al, 2000). Exons E1 or F are spliced to exon E2, which is subsequently spliced to exon 2, creating an mRNA that lacks exon 1 (Dexon1).…”
Section: Barx2 and E 2 Treatment Alter The Expression Of Different Esmentioning
confidence: 99%
“…In particular, an mRNA lacking exon 1 is translated from an initiation codon in exon 2, generating a truncated 46 kDa protein (ESR1-46) that lacks the N-terminal ligand-dependent activation function. ESR1-46 does not activate gene expression in response to estrogen and can function in a dominant-negative manner by binding to ESR1-66 and blocking its liganddependent activation function (Flouriot et al, 2000;Metivier et al, 2004). ESR1-46 is expressed in breast cancer cell lines, mammary gland and osteoblasts (Fasco et al, 2000;Flouriot et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation